Fotografia jako narzędzie mediatyzacji wojny w mediach społecznościowych – na przykładzie fotografii konfliktu na wschodniej Ukrainie - Szulich-Kałuża, Justyna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The subject of the article relates to reflections on photography as a media tool, disseminating knowledge about contemporary war conflicts on the example of the photographs of conflict in eastern Ukraine. To analyse the photography quantital content-analysis and semiotic analysis techniques were employed. For the needs of quantitative analysis, a categorizing key was elaborated, which included form and substance categories to describe photographs. The detailed analysis covered all the photos that users posted on Facebook and Vkontakte social networking posts from 1.04.2014 to 31.12.2014. In all, the research material consisted of 197 randomly selected photographs, 112 published on Facebook and 85 on Vkontakte. The results of own analyses were used to find answers to more detailed questions, which can be closed in the following problem areas: stylistic and composite forms of photographic documentation of warfare, realism or manipulation in photographic narratives of the war, characteristics of war strategy in social media.